Rūam kotmai læ rabīap kīeokap kānl̄ưaktang samāchik Saphā Phūth̄æn Rātsad̨̄on, Ph̨̄o. S̨̄o. 2539 (Krom Kānpokkhr̨̄ong, Krasūang Mahātthai, 1996)
Laws and regulations related to elections of members of House of Representatives, Thailand.